Allogeneic Stem Cells From Deciduous Teeth in Treatment for Periodontitis in Miniature Swine. Issue 6 (1st June 2014) - Fu, Xiaoru; Jin, Luyuan; Ma, Ping; Fan, Zhipeng; Wang, Songlin
Abstract : Background: Regeneration of lost periodontium in periodontitis is a challenge in that alveolar bone, cementum, and periodontal ligament need to be restored to their original architecture. Stem cells from exfoliated deciduous teeth (SHEDs) appear to be an attractive candidate for periodontium tissue regeneration. Previously, the authors successfully regenerated periodontal defects using autologous and allogeneic periodontal ligament stem cells (PDLSCs). The purpose of the present study is to investigate the ability of allogeneic SHEDs to regenerate lost periodontium in a swine periodontitis model. Methods: Animal models of periodontitis were established in miniature pigs, and allogeneic stem cells were isolated from miniature pig deciduous teeth (SPDs). The animal models were treated with SPDs plus hydroxyapatite/tricalcium phosphate (HA/TCP). Allogeneic PDLSCs plus HA/TCP or HA/TCP alone were set as positive control or control, respectively. Clinical assessments, computed tomography (CT) scanning, and histologic examination were used to evaluate the outcome of tissue regeneration. Results: Clinical indices including probing depth, gingival recession, and attachment loss showed significant restoration in the SPD and PDLSC treatment groups, compared to the HA/TCP group 12 weeks post‐transplantation. Meanwhile, CT scans showed that 75% of the samples had successful hard‐tissue regeneration in both PDLSC and SPD groups, compared to the HA/TCP group, where the success rate was only 25%. In addition, histologic examination demonstrated that SPD and PDLSC treatment brought about remarkable regeneration of periodontal tissues, whereas periodontal regeneration was rare in the HA/TCP group. Conclusions: Allogeneic SPDs can effectively repair hard and soft tissue loss brought about by periodontitis in a swine model. Allogeneic SHEDs, which are easily accessible, may be applied to treat periodontitis in clinics in the future.